The Existence of Agile Governance in the Public Sector in Indonesia: A Systematic Literature Review - Farchan Maulana; Muhammad Chasan Amrulloh; Jusuf Irianto (Jurnal Administrasi Publik, 2026)
Agile governance has emerged as an important approach for increasing the adaptability and responsiveness of public organizations in dealing with rapid environmental, technological, and societal changes. Although studies on agile governance have grown significantly, evidence regarding its implementation in Indonesia’s public sector remains fragmented and has not been systematically synthesized. This study aims to analyze the existence of agile governance in Indonesia’s public sector and assess the extent to which the six meta-principles of agile governance are reflected in existing empirical studies. To achieve this objective, a Systematic Literature Review (SLR) was conducted following a structured screening and selection process using the Scopus and ScienceDirect databases. The selected literature was analyzed based on Luna’s six agile governance meta-principles: Good Enough Governance, Business-Driven, Human-Focused, Based on Quick Wins, Systematic and Adaptive Approach, and Simple Design and Continuous Refinement. The findings indicate that agile governance has been implemented in several areas of Indonesia’s public sector, particularly in digital transformation, public service delivery, disaster management, and intergovernmental coordination. However, the implementation of agile governance remains uneven. Human-Focused, Good Enough Governance, and Systematic and Adaptive Approach principles appear relatively strong, while Business-Driven, Based on Quick Wins, and Simple Design and Continuous Refinement principles are less consistently evident. The study also identifies persistent challenges, including bureaucratic rigidity, policy inconsistency, coordination problems, and limited adaptive capacity. This research contributes to the literature by providing a comprehensive synthesis of agile governance implementation in Indonesia’s public sector and highlighting areas requiring further institutional development.